Simulation-based optimisation and analysis for CO2 pipeline transportation system with uncertainties. (2018) - Tian, Qunhong; Zhao, Dongya; Li, Zhaomin; Zhu, Quanmin
Carbon capture, utilisation and storage (CCUS) technology is one of the main measures to achieve greenhouse gas emission reduction. As an important link of CCUS technology, pipeline transportation is the most cost-effective transportation mode to transport large-scale CO2 . In order to investigate the effect caused by parameter uncertainties, a simulation-based techno-economic optimisation model is proposed to describe the complicated pipeline design problem in this paper, which takes into account engineering and economic modelling. Penalty function and Newton's method are presented to optimise the pipeline, based on the obtained optimal inlet pressure, pipe diameter, wall thickness, number of pump stations and levellised cost, and uncertain parameters analysis is presented to research the pipeline optimisation design. Based on the pipeline optimisation modelling, simulation results demonstrate the effectiveness of the proposed optimisation approach, and analysis gives the levellised cost change caused by uncertainties, which can provide a theoretical basis to design pipeline.